Study of Some Production Indicators of Syrian Local Poultry in Coastal Conditions - Hmeshe, Mohsen (International Journal of Poultry Science, 2012)
The sexual maturity, egg quantity and productivity of 175 Syrian local hens of primary flock were studied for 150 days. Our results indicated that the age of sexual maturity was 206 days. The egg quantity average of the flock was 73.04 eggs, while it was 82.12 and 60.38 eggs for selected hens (egg quantity) and discarded respectively. The percentage of egg production was 49%. The average of egg weight was 50.85 gr. Egg mass amounted 24.58 gr/hen/day, while the egg productivity was 0.49 egg/hen/day. The Feed Conversion Ratio (FCR) was 4.6 kg. fodder/1 kg eggs. These results showed that the selected hens were better than discarded ones. Therefore, it is necessary to continue selection program to produce the first selected generation (F1).